Intertextuality and Its Role in the Classroom - Rechin, Sophia (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Within the English language arts classroom, our students come to us with a background of different experienceS or lack of such experiences. They have all read different books, seen different movies, been to different places, and lived vastly different lives. When a student approaches a new text, they bring to it all their previous experience and interactions. This manuscript will explore the ways in which these experiences, and the idea of intertextuality, can be used within the English language arts classroom in order to enhance things like student engagement and reading comprehension. We will look at ways in which it can be integrated within curriculum and used to the student’s advantage.